Marketing-Driven Enhancements in Student Experience and Their Influence on University Reputation - Arun Seeralan Balakrishnan (Escalate : Economics and Business Journal, 2025)
Abstract: This study explores the effect of innovative marketing strategies on university reputation, with perceived value acting as a mediating variable, within the context of Universitas Negeri Makassar. A quantitative approach using structural equation modeling via Smart PLS was employed to examine four independent variables: brand positioning and image strategy, digital marketing strategy, gamified engagement tools, and student co-creation participation. Findings indicate that brand positioning and digital marketing significantly influence perceived value and university reputation. Meanwhile, gamified engagement and student co-creation primarily impact perceived value but do not directly affect reputation. Perceived value has a strong and statistically significant effect on university reputation, mediating the relationship between several marketing strategies and institutional reputation. The study underscores the strategic value of enhancing students' perceived educational value through student-centered marketing to build reputational capital. It contributes to higher education marketing literature and offers practical insights for university leaders aiming to strengthen institutional image.